Transgender EuroStudy : legal survey and focus on the transgender experience of health care - Whittle, Stephen; Turner, Lewis; Combs, Ryan; Rhodes, Stephenne (Brussel Berlin : ILGA-Europe TransGender Europe, 2008)
Fonds Suzan Daniel (FSD)
Engels
Monografie